A revised classification for the neopasiphaeine line, with description of new species of the bee tribe Lonchopriini (Apidae, Colletinae) - Melo, Gabriel A. R. (Acta Biológica Paranaense, 2022)
Two new species of Lonchopriini from Brazil are proposed, one belonging to Camposapis, a genus recently proposed in honor of professor Lucio Campos, and the other one to Ctenosibyne, a genus thus far believed to be monotypic. Camposapis catarinae sp. nov. is described based on females and males collected in Santa Catarina, while Ctenosibyne singularis sp. nov. is proposed based on a single male collected in Paraná. As a way to introduce the new names the current classification of the Colletinae sensu lato is discussed and a new system for the tribes composing this important element of our bee fauna is proposed. Three phyletic lines are recognized for the Colletinae: the colletine, diphaglossine and neopasiphaeine lines. In the neopasiphaeine line, the following tribes are recognized: Anthoglossini (Australia), Eulonchopriini (New World), Lonchopriini (South America), Neopasiphaeini (Australia), and Trichocolletini (Australia). It is also argued that changes to classification systems should be based on solid phylogenetic evidence and that any urge to name all possible lineages will certainly result in redundant names that are likely to be abandoned in the future. Well-established taxonomic and nomenclatural practices should be strictly followed in order to avoid what has been called as taxonomic vandalism.